2016
DOI: 10.1111/inm.12224
|View full text |Cite
|
Sign up to set email alerts
|

Helpful and unhelpful responses after suicide: Experiences of bereaved family members

Abstract: Individuals who are bereaved by suicide and other traumatic natured deaths are thought to be at greater risk of psychological complications, than people bereaved by other means. While it is recognized that interventions can influence the bereavement process, there remains limited communications about both helpful responses and those that may adversely influence the grieving process for the suicide bereaved. This paper presents findings from a narrative study, which sought the experiences of family members afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 22 publications
0
70
0
4
Order By: Relevance
“…Research suggests that a greater extent of social support may function as a protective factor against the development of PGD (Burke, Neimeyer, & McDevitt-Murphy, 2010;Hibberd et al, 2010). However, survivors also report stigma and insensitive reactions pointing to a potentially harmful social environment (Feigelman et al, 2009;Peters, Cunningham, Murphy, & Jackson, 2016).…”
Section: Previous Research On Risk Factors and Correlates Of Pgdmentioning
confidence: 99%
“…Research suggests that a greater extent of social support may function as a protective factor against the development of PGD (Burke, Neimeyer, & McDevitt-Murphy, 2010;Hibberd et al, 2010). However, survivors also report stigma and insensitive reactions pointing to a potentially harmful social environment (Feigelman et al, 2009;Peters, Cunningham, Murphy, & Jackson, 2016).…”
Section: Previous Research On Risk Factors and Correlates Of Pgdmentioning
confidence: 99%
“…However, qualitative (Jordan & Neimeyer, 2003;Schut & Stroebe, 2005;Schut, Stroebe, Van den Bout, & Terheggen, 2001) and quantitative reviews (Currier, Neimeyer, & Berman, 2008;Murphy, Lipp, & Powles, 2012;Waller et al, 2015) have found that little empirical support exists for the effectiveness of universal interventions employed with the majority of people who suffer from uncomplicated grief. Peters, Cunningham, Murphy, and Jackson (2016) have reviewed harmful and beneficial interventions reported by family members affected by the suicide of a loved one. Peer-support groups were among the higher rated interventions because they allow sharing memories of their loved ones with others, and participants can reconstruct meaningful relationships with their inner and social worlds.…”
mentioning
confidence: 99%
“…Most participants were related in some way to the deceased. This included close family members, such as parent, sibling, children, spouse (Demi & Howell, ; Van Dongen, , , ); spouses (Constantino & Bricker, ; Constantino et al., ); parent and sibling (Begley & Quayle, ; Fielden, ; Hoffman et al, ; Tzeng, Su, Chiang, Kuan, & Lee, ); parent, spouse (Peters, Cunningham, Murphy, & Jackson, ,b; Peters, Murphy, & Jackson, ; Supiano, ); and other relatives (Hoffmann, ; Peters et al., Peters et al., ,b; Tzeng et al., ; Wilson & Marshall, ). One study included friends (Hoffmann, ).…”
Section: Methodsmentioning
confidence: 99%
“…Survivors reflected on support and survival strategies which seemed to vacillate from helpful to not helpful. Needing, and seeking formal support, they lacked satisfaction receiving support (Peters et al, 2016a;Wilson & Marshall, 2010), especially from health care personnel (Peters et al, 2013) and police who met them with disbelief (Van Dongen, 1993). However, they experienced helpfulness from clergy, co-workers and family (Van Dongen, 1993).…”
Section: Synthesised Concept 3 Enduring Being Burdened-unburdenedmentioning
confidence: 99%